PARADIGMA KONSELING BERPERSPEKTIF GENDER - Zainal Abidin, S.Psi., M.Si., Yuliati Hotifah, S.Psi. (EGALITA, 2006)
This paper suggests that stereotype towards women is the basic root of gender inequalityÂ  problem. Consequently, women may face subordination, marginalization, discrimination, double burden and sexual violence.This gender bias problem also happens in Therapy practice where social cognition in conselling process constructs the psychological problem of women in sexism perception which puts women as the main cause of problem. Hence, the theraphy practice should apply gender conselling approach to help the clients to increase their gender awareness as well as their gender sensitivity. Broadening the discourse on gender role will increase therapists skill to overcome the obstacles for career development based on equal gender relation.